The longitudinal use of EmPHasis-10 and CAMPHOR questionnaire health-related quality of life scores in patients with pulmonary arterial hypertension and chronic thromboembolic pulmonary hypertension. (September 2021) - Hendriks, Paul M.; van Thor, Mitch C.J.; Wapenaar, Monique; Chandoesing, Prewesh; van den Toorn, Leon M.; van den Bosch, Annemien E.; Post, Marco C.; Boomars, Karin A.
Abstract: Background: Health-related quality of life (HRQoL) is impaired in patients with pulmonary hypertension (PH). The EmPHasis-10 and CAMPHOR questionnaires are developed to evaluate HRQoL specifically in patients with PH. Data on the longitudinal use of both questionnaires are still limited. We evaluated the longitudinal value of both questionnaires and established minimal clinically important differences (MCID). Methods: Sixty-one treatment naïve pulmonary arterial hypertension or chronic thromboembolic patients were prospectively included. Patients were treated according to the current ESC/ERS guidelines. We compared EmPHasis-10 and CAMPHOR scores between baseline, 6 and 12 months of follow-up and evaluated the correlation between these scores and a 5-scale symptom severity score, 5-scale overall health score, NYHA-classification, 6 min walk test distance (6MWD), NT-proBNP and echocardiographic parameters. Results: After one year of treatment a significant reduction in EmPHasis-10 score and CAMPHOR QoL and symptoms domain score was observed. Moderate to good correlations were observed between the questionnaires and the overall-health and symptom severity score and 6MWD. No relevant correlations were seen between the questionnaires and NT-pro-BNP and echocardiographic parameters. EmPHasis-10 scores showed strong correlations with all CAMPHOR domains. The MCID for the EmPHasis-10 questionnaire was −8. The MCIDs for the CAMPHOR domains were: activity −3, symptoms −4, QoL −3. Conclusion: The EmPHasis-10 and CAMPHOR questionnaires are valid tools for the longitudinal measurement of HRQoL in patients with PH. The much shorter EmPHasis-10 correlates well with the CAMPHOR domain scores and with the clinical endpoints and it may be easier to use in daily practice. Highlights: EmPHasis-10 and CAMPHOR are suitable for longitudinal PH-specific QoL measurement. EmPHasis-10 and CAMPHOR scores correlated well with clinical anchor points. EmPHasis-10 scores correlated well with CAMPHOR scores. Improvement of QoL was seen following treatment initiation in PAH and CTEPH. Acceptable MCID's were determined for both questionnaires.